Halal Fashion Consumption: Understanding Determinants of Brand Loyalty among Hijab Consumers - Baharuddin, Farrah Nadia; Mokhlis, Safiek; Mokhtar, Noor Fadhiha (International Review of Management and Marketing, 2025)
Hijab fashion represents a vital segment within the halal fashion industry, marked by intense competition and rapid growth. This study aims to examine the determinants of brand loyalty in the context of hijab fashion by developing and testing a conceptual model. Brand loyalty is recognized as a critical strategic asset, offering competitive advantage and long-term relevance in a dynamic retail environment. However, maintaining such loyalty presents ongoing challenges. Grounded in the Stimulus–Organism–Response (S-O-R) framework and the Satisfaction–Loyalty model, this study investigates the influence of retail brand experience on brand loyalty, with brand satisfaction and brand trust serving as mediating variables. Data were collected using a purposive sampling method through mall intercept surveys, yielding 500 valid responses. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that retail brand experience significantly influences brand satisfaction and brand loyalty, with a serial mediation effect through brand satisfaction and brand trust. These findings provide valuable insights for hijab fashion brands seeking to build effective marketing strategies that foster brand loyalty and support long-term business sustainability in the competitive hijab fashion in retail landscape.